2012
DOI: 10.1139/x2012-028
|View full text |Cite
|
Sign up to set email alerts
|

Tree-ring investigations into changing climatic responses of yellow-cedar, Glacier Bay, Alaska

Abstract: Yellow-cedar (Callitropsis nootkatensis (D. Don) Örsted ex D.P. Little) is in a century-long decline coinciding with the end of the Little Ice Age (LIA). The leading hypothesis explaining this decline is a decrease in insulating snowpack due to warming and increased susceptibility to damaging frosts in the root zone. A ring-width series from yellow-cedar on Excursion Ridge (260 m a.s.l.) in Glacier Bay National Park and Preserve, Alaska, and another from trees on Pleasant Island (150 m a.s.l.) in the Tongass N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 14 publications
4
18
0
Order By: Relevance
“…By the second half of the 20th century both sites had become strongly negatively correlated to temperature. This strong negative response to warming by the yellow cedar together with a positive relationship with total March and April precipitation suggested that the yellowcedar sites may be susceptible to decline and is consistent with the hypothesis that the yellow-cedar decline is linked to decreased snowpack (Wiles et al, 2012).…”
Section: Discussionsupporting
confidence: 85%
“…By the second half of the 20th century both sites had become strongly negatively correlated to temperature. This strong negative response to warming by the yellow cedar together with a positive relationship with total March and April precipitation suggested that the yellowcedar sites may be susceptible to decline and is consistent with the hypothesis that the yellow-cedar decline is linked to decreased snowpack (Wiles et al, 2012).…”
Section: Discussionsupporting
confidence: 85%
“…While no mountain hemlock sites have become negatively correlated to temperature as the yellow cedars have, the patterns in growth response to climate observed over the 20th century at the low-elevation mountain hemlock sites resemble those observed by Wiles et al (2012) from the LIA to the first half of the 20th century in the higher elevation cedar site in Glacier Bay. This suggests that the change in growth response of both species is related and elevationally determined, the effects traveling upslope with time and warming.…”
Section: Discussionmentioning
confidence: 60%
“…low temperature) and are now tracking the rising air temperature (Fritts, 1976;Holtmeier and Broll, 2007). Wiles et al (2012) found a shift in the relationship between yellow-cedar growth and January-July temperature since the LIA. A slight negative correlation to temperature was present at the lowelevation site at the end of the LIA, while the higher-elevation site was significantly positively correlated to temperature.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Extensive work has been done testing this hypothesis and exploring the forest dynamics and ecology associated with the decline (Oakes et al, 2014(Oakes et al, , 2015 driven by concerns of species loss and determination of whether the species is endangered (Buma et al, 2017;Barrett andPattison, 2017, Bidlack et al, 2017). Dendroclimatic studies of RW in southeast Alaska have shown that the growth response of yellow-cedar can be spatially and temporally complex (Beier et al, 2008;Wiles et al, 2012) and, in general, results have not been promising for climate reconstruction. Beier et al (2008) analyzed RW from declining cedar sites in southeast Alaska and from the healthy stand at Cedar Lake, one of our study sites.…”
Section: Introductionmentioning
confidence: 99%